'Geoengineering' – taking control of our planet's climate. (1st July 2009) - Irvine, Peter; Ridgwell, Andy
There is international consensus that 'dangerous' climate change must be avoided. Yet without radical changes in energy sources and usage and global economies, changes that so far society has been unable or unwilling to make, it seems highly likely that we will start to experience unacceptably damaging and/or societally disruptive global environmental change later this century. What actions can be taken to safeguard future environmental quality, ecosystems, agriculture, economy, and society? A new science – 'geoengineering' – that until recently would have seemed pure science fiction, promises an alternative way of temporarily regaining control of climate. Colossal engineering schemes to shade the sun, make the atmosphere hazier, modify clouds, even throw iron into the ocean, are all being promoted as possible ways out of our dilemma. This article considers the state of this new science, and its implications for society.